Biological correlates of adult cognition. Midlife in the United States (MIDUS) - Karlamangla, Arun S. (2013)
Multiple biological processes are related to cognitive impairment in older adults, but their combined impact on cognition in midlife is not known. Using an array of measurements across key regulatory physiological systems and a state-of-the-art cognition battery that is sensitive to early changes, on a large, national sample of middle-aged and older adults, we examined the associations of individual biological systems and a combined, multi-system index, allostatic load, with cognitive performance. Allostatic load was strongly inversely associated with performance in both episodic memory and executive function. Of seven biological systems, only the cardiovascular system was associated inversely with both; inflammation was associated inversely with episodic memory only, and glucose metabolism with executive function only. The associations of allostatic load with cognition were not different by age, suggesting that the implications of high allostatic load on cognitive functioning are not restricted to older adults. Findings suggest that a multi-system score, like allostatic load, may assist in the identification of adults at increased risk for cognitive impairment at en early age.